(untitled) (Fiep Bulletin - online, 2014)
Introduction: More and more researches point out that the exercise is an indispensable factor for a better health and quality of life and the proper functioning of our body. Objective: Determining what the key factors that motivate people to practice physical exercises in gyms are. Materials and Methods: A descriptive transversal study performed in 2012 in 05 gyms in Cascavel, in the west of the state of Paraná, in the south of Brazil. The study population consisted of all people, male and female, in the age group between 18-50 years old. The sample consisted of 576 individuals (306 males and 270 females). The questionnaire was designed by the researchers and referred to the factors that led the people to gyms. Data were stored in the program SPSS version 15.0. We used descriptive statistics with values ??of absolute and relative frequency of the responses that were obtained. Results: The results showed that most practitioners feel well with the physical exercises, and those attend the gyms four or more times per week. Conclusion: The main reason that leads people to attend the gyms are the aesthetic factors, such as weight loss, improvement of physical appearance and muscle definition.